Design, synthesis and biological evaluation of benzamide and phenyltetrazole derivatives with amide and urea linkers as BCRP inhibitors. Issue 20 (15th October 2017) - Gujarati, Nehaben A.; Zeng, Leli; Gupta, Pranav; Chen, Zhe-Sheng; Korlipara, Vijaya L.
Graphical abstract: Abstract: Breast cancer resistant protein (BCRP/ABCG2), a 72 kDa plasma membrane transporter protein is a member of ABC transporter superfamily. Increased expression of BCRP causes increased efflux and therefore, reduced intracellular accumulation of many unrelated chemotherapeutic agents leading to multidrug resistance (MDR). A series of 31 benzamide and phenyltetrazole derivatives with amide and urea linkers has been synthesized to serve as potential BCRP inhibitors in order to overcome BCRP-mediated MDR. The target derivatives were tested for their cytotoxicity and reversal effects in human non-small cell lung cancer cell line H460 and mitoxantrone resistant cell line H460/MX20 using the MTT assay. In the benzamide series, compounds6 and7 exhibited a fold resistance of 1.51 and 1.62, respectively at 10 µM concentration which is similar to that of FTC, a known BCRP inhibitor. Compounds27 and31 were the most potent analogues in the phenyltetrazole series with amide linker with a fold resistance of 1.39 and 1.32, respectively at 10 µM concentration. For the phenyltetrazole series with urea linker, 38 exhibited a fold resistance of 1.51 which is similar than that of FTC and is the most potent compound in this series. The target compounds did not exhibit reversal effect in P-gp overexpressing resistant cell line SW620/Ad300 suggesting that they are selective BCRP inhibitors.